What do Indonesian Gen Z look for when booking accommodation? - Devi, Ni Kadek Cintya Laksmi; Prayoga, I Komang Wiramas (Universitas Pendidikan Nasional, 2025)
Despite extensive research on factors influencing consumer decisions in booking accommodation, limited attention has been given to understanding Generation Z's specific behavior when using digital platforms for this purpose. Additionally, inconsistencies in previous findings regarding the determinants of Generation Z's purchase intentions highlight the need for a more focused and contextualized investigation. This study aims to identify the key factors that shape Generation Z's intention to purchase accommodations through the Traveloka platform in Indonesia. A quantitative research methodology was employed in this study, with data collected from a diverse group of 179 respondents representing various regions in Indonesia. The collected data were analyzed using SPSS software to assess the relationships between the variables. The findings reveal that perceived usefulness, perceived ease of use, and attitude significantly influence Generation Z's intention to purchase accommodation through Traveloka. These results offer practical insights for Traveloka and industry stakeholders in the tourism sector. To enhance perceived usefulness and perceived ease of use, Traveloka is encouraged to implement continuous improvements to its features and user interface. Furthermore, these findings provide a deeper understanding of Generation Z's preferences when booking accommodation online, enabling industry practitioners to develop more effective marketing strategies and refine their service offerings to align with the evolving expectations of this consumer segment.